2013
DOI: 10.1085/jgp.201210876
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ oscillations, Ca2+ sensitization, and contraction activated by protein kinase C in small airway smooth muscle

Abstract: Protein kinase C (PKC) has been implicated in the regulation of smooth muscle cell (SMC) contraction and may contribute to airway hyperresponsiveness. Here, we combined optical and biochemical analyses of mouse lung slices to determine the effects of PKC activation on Ca2+ signaling, Ca2+ sensitivity, protein phosphorylation, and contraction in SMCs of small intrapulmonary airways. We found that 10 µM phorbol-12-myristate-13-acetate or 1 µM phorbol 12,13-dibutyrate induced repetitive, unsynchronized, and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 40 publications
1
49
0
Order By: Relevance
“…07069). Mouse lung slices were prepared as previously described (5,34). Briefly, male C3H mice (8 -12 wk) were killed with pentobarbital (40 mg/kg ip) and the chest cavity was opened to allow for cannulation of the trachea.…”
Section: Effect Of Sh-053-2=f-r-ch3 On Methacholine-mediated Contractmentioning
confidence: 99%
See 2 more Smart Citations
“…07069). Mouse lung slices were prepared as previously described (5,34). Briefly, male C3H mice (8 -12 wk) were killed with pentobarbital (40 mg/kg ip) and the chest cavity was opened to allow for cannulation of the trachea.…”
Section: Effect Of Sh-053-2=f-r-ch3 On Methacholine-mediated Contractmentioning
confidence: 99%
“…Measurements of changes in small-airway cross-sectional lumen area (lumen area hereafter) and the fluorescent measurements of [Ca 2ϩ ]i in ASM cells were performed as previously described (34). Briefly, lung slices were mounted in a custom-made perfusion chamber and airways were visualized by use of a ϫ10 objective.…”
Section: Effect Of Sh-053-2=f-r-ch3 On Methacholine-mediated Contractmentioning
confidence: 99%
See 1 more Smart Citation
“…The potentiation observed by Boterman and colleagues and Nakahara and colleagues could be attributed to decreased CPI-17 phosphorylation downstream of PKC or Rho kinase inhibition. Recently, Mukherjee and colleagues (44) found that PKC activation in the airway leads to CPI-17 phosphorylation and increases in MLC 20 phosphorylation. Here, we have shown that 6-gingerol, 8-gingerol, and 6-shogaol prevent ACh-induced phosphorylation of CPI-17.…”
Section: Mlck/mlcp In Contraction and Relaxation-role For Accessory Pmentioning
confidence: 99%
“…19 In another study, inhibition of PKC by calphostin-C, prevented proliferation of bovine tracheal smooth muscle cells following activation of mannose receptors by β-hexosaminidase and also abolished Ca 2+ -dependent and -independent PKC activity 20 which suggests involvement of different isoenzymes of PKC.…”
mentioning
confidence: 93%